Incaísmo, indigenismo y gamonalismo: Rumi Maki from Three Rethorical Types of Representation - Coca Vargas, César (2021)
On December 2, 1915, in Azángaro (Puno), there was a peasant uprising on the San José farm. The sources that recorded this event indicate that an Inca-inspired leader who called himself “Rumi Maki Ccori Zoncco” participated in said rebellion. Contemporary writers and journalists and even subsequent researchers have written about this legendary figure, whose real name might have been Teodomiro Gutiérrez Cuevas (1864-¿?). Although in some cases we can observe analyses from a cultural approach (incaistas or indigenistas, for example), I believe that there has been no detailed explanation of the cultural implications from those who dedicated lines to Rumi Maki’s figure. For this reason, my main purpose is to read the San José uprising in that direction. To this end, I will use three rhetoric modalities: the incaista (José Carlos Mariátegui), the indigenista (Dora Mayer, Manuel González Prada, Francisco Chukiwanka) and the gamonalista (Sebastián Urquiaga, Angelino Lizares). From here on, I will analyze the the rethorical type of each writing modality that represented Rumi Maki.